The Development of Komfun CT Learning Media Based on Scratch to Enhance Computational Thinking Skills - Yuli Bangun Nursanti; Rachma Lutfiana (PAEDAGOGIA, 2025)
This research is motivated by the low level of students' computational thinking skills in mathematics learning, particularly in the topic of function composition. To address this issue, a Scratch-based learning media was developed with the aim of helping students understand the concept of function composition while also enhancing their computational thinking skills. The aim of this study is to produce Komfun CT learning media based on Scratch for function composition material. The research was conducted in the 2024/2025 academic year using the Research & Development (R&D) method based on the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The quality of the developed media must meet the criteria of validity, practicality, and effectiveness. The instruments used in this study include observation sheets, interview guidelines, questionnaires, and tests. The observation sheets were used to obtain information about mathematics learning activities conducted by the teacher at school. The interview guidelines were used with students to collect qualitative data regarding the practicality of the developed media. The questionnaires consisted of a student response questionnaire, a material expert questionnaire, and a media expert questionnaire. Finally, the computational thinking test, which included a pre-test and post-test, was used to assess students’ computational thinking skills before and after using the media.The results showed that: (1) the media developed using the ADDIE model successfully produced Komfun CT learning media based on Scratch; (2) the Komfun CT learning media was declared feasible based on expert validation (material and media), covering aspects of validity, practicality, and effectiveness; (3) the developed media met the validity criteria with an average percentage of 93.86%. The practicality test results showed an average percentage of 83.60% from student responses. The effectiveness test based on N-Gain analysis showed an average gain score of 85.43%, indicating that the media is effective in enhancing students’ Computational Thinking.